Antitumor and cytotoxic activity of Kielmeyera coriacea mart. Zucc. and Pyrostegia venusta (ker-gawl.) Miers extracts - Silva, Regildo Márcio Gonçalves da [UNESP]; Rodrigues, Débora Thaís Miranda [UNESP]; Valadares, Fillipi [UNESP]; Oliva Neto, Pedro de [UNESP]; Santos, Lucinéia dos [UNESP]; Silva, Luciana Pereira [UNESP] (Academic Journals, 2012)
This study aimed to investigate the antitumor and cytotoxicity activities of Kielmeyera coriacea and Pyrostegia venusta extracts. Therefore, the hydroalcoholic extracts of P. venusta flowers and K. coriacea leaves were prepared. The extracts were evaporated and the dry extracts were diluted at concentrations of 1.0, 0.1, 0.01 and 0.001 mg/ml for carrying out the bioassays. Artemia salina eggs were incubated in saline solution at 28°C for 24 h. The larvae were treated with different extracts concentrations and the mortality was evaluated after 24 and 48 h. Five discs of potato were placed in Petri dishes and 50 μl of inoculum of Agrobacterium tumefaciens were added to it at 28°C for 24 h incubation. So, 50 μl of the extracts in different concentrations were added. Positive and negative controls were made. The P. venusta and K. coriacea extracts did not show statistically significant acute toxicity. K. coriacea extract showed (mean% of tumor ± standard deviation) 15.30 ± 3.24, 6.34 ± 3.82, 7.57 ± 2.92 and 5.77 ± 2.85 and P. venusta showed 25.82 ± 5.15, 38.40 ± 8.28, 15.75 ± 4.44 and 13.38 ± 7.92, with their concentrations for the antitumor bioassay, and the positive control showed 25.80 ± 6.14. According to the obtained results it was established that the K. coriacea and P. venusta extracts showed antitumor activity but did not show significant cytotoxic activity in A. salina test.
Keywords: Kielmeyera coriacea; Pyrostegia venusta; Agrobacterium tumefaciens; antitumor activity; cytotoxic activity